Synthesis of Substituted 1,2,4-Triazole Containing Novel Small Molecules by Using Microwave - J. Gohil, Chirag; N. Noolvi, Malleshappa (Journal of Sustainable Materials Processing and Management, 2023)
Green chemistry finds its most promising use in the synthesis of compounds using ecologically friendly, non-hazardous, non-irritant, gentle, and reproducible catalysts and solvents. The adoption of green chemistry approaches has recently been shown to significantly reduce chemical waste and reaction times in a number of organic synthesis processes. The objective of this research work is to develop an eco-friendly method for the Substituted 1,2,4-Triazole containing novel small molecules. The approach makes use of acid as starting material on reaction with hydrazine forms Acetyl-hydrazide. On condensation with nitrile and subsequent ring closure forms substituted 1,2,4-Triazole derivatives.  This research work describes the synthesis of thirty-two unique 1,2,4-triazole containing novel small molecules. It has been shown that this technique is superior to other synthetic methods in terms of reaction time, yield, and energy efficiency along with use of green chemistry and microwave.